Pengaruh Word Of Mouth terhadap Keinginan Melakukan Vaksinasi Covid-19 pada Usia Produktif 15-65 Tahun - Yuliana Putri; Rizca Haqqu (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2023)
The purpose of this study was to measure and answer the question whether Word of Mouth influences the desire to vaccinate against COVID-19 at a productive age. This research method uses a variety of test variables in order to get accurate results. The results of this study are based on the results of the determination test (R square), the results of the R square test found that Word of Mouth has an effect of 0.546. It can be stated that Word of Mouth affects the desire to vaccinate by 54.6% influenced by other variables that are not present in this study. And the results of the t test found that tcount > ttable (4.971 > 1.98) then H0 was rejected statistically. From the results of the t test, the significant value is less than 0.05 (0.000 <0.05), which can be interpreted as having a fairly close influence between Word of Mouth on the desire to vaccinate. The conclusion of the study is that Word of Mouth affects a person's desire to vaccinate against Covid-19. Keywords: Covid-19, Vaccination, Word of Mouth